Altered astrocyte morphology and vascular development in dystrophin‐Dp71‐null mice. Issue 5 (29th December 2015) - Giocanti‐Auregan, Audrey; Vacca, Ophélie; Bénard, Romain; Cao, Sijia; Siqueiros, Lourdes; Montañez, Cecilia; Paques, Michel; Sahel, José‐Alain; Sennlaub, Florian; Guillonneau, Xavier; Rendon, Alvaro; Tadayoni, Ramin
Abstract : Understanding retinal vascular development is crucial because many retinal vascular diseases such as diabetic retinopathy (in adults) or retinopathy of prematurity (in children) are among the leading causes of blindness. Given the localization of the protein Dp71 around the retinal vessels in adult mice and its role in maintaining retinal homeostasis, the aim of this study was to determine if Dp71 was involved in astrocyte and vascular development regulation. An experimental study in mouse retinas was conducted. Using a dual immunolabeling with antibodies to Dp71 and anti‐GFAP for astrocytes on retinal sections and isolated astrocytes, it was found that Dp71 was expressed in wild‐type (WT) mouse astrocytes from early developmental stages to adult stage. In Dp71‐null mice, a reduction in GFAP‐immunopositive astrocytes was observed as early as postnatal day 6 (P6) compared with WT mice. Using real‐time PCR, it was showed that Dp71 mRNA was stable between P1 and P6, in parallel with post‐natal vascular development. Regarding morphology in Dp71‐null and WT mice, a significant decrease in overall astrocyte process number in Dp71‐null retinas at P6 to adult age was found. Using fluorescence‐conjugated isolectin Griffonia simplicifolia on whole mount retinas, subsequent delay of developing vascular network at the same age in Dp71‐null mice was found. An evidence that the Dystrophin Dp71, a membrane‐associated cytoskeletal protein and one of the smaller Duchenne muscular dystrophy gene products, regulates astrocyte morphology and density and is associated with subsequent normal blood vessel development was provided. GLIA 2016;64:716–729 Main points: Dystrophin Dp71, a membrane‐associated cytoskeletal protein and the major Duchenne muscular dystrophy gene product in the retina, regulates astrocyte morphology and density and is associated with subsequent normal blood vessel development.